Interest in Being an Ally Against Violence Toward Women: A Survey of Barbers in Black Communities - Howard, Stephenie (Journal of interpersonal violence, 2025)
To what extent are barbers willing to act as allies in addressing the abuse of women within Black communities? The study focused on barbers primarily serving Black clients. To gage the cultural viability of utilizing barbershops as intervention sites for intimate partner violence, the authors of this article conducted surveys among barbers in Black communities. The surveys explored the barbers’ interest in and capability to act as allies against violence targeting Black women. The study revealed a strong interest among barbers in assuming the role of allies, accompanied by an endorsement of a critical skill set that positions them effectively in intervening against abusive behaviors. Additionally, the research identified key elements necessary for the development of ally programs tailored for barbers in Black communities. Barbers emerged as crucial resources in the effort to combat violence against women in Black communities. Recognizing their specific interests and addressing their unique needs is essential for the success of programs harnessing their potential in this capacity.